FEATURES OF INFECTED VERSUS UNINFECTED CHEMICAL PROFILES RELEASED FROM HUMAN EXUDATES - RATIU, Ileana-Andreea; LIGOR, Tomasz; MONEDEIRO, Fernanda; AL-SUOD, Hossam; BOCOȘ-BINȚINȚAN, Victor; SZELIGA, Jacek; JACKOWSKI, Marek; BUSZEWSKI, Boguslaw (Studia Universitatis Babeș-Bolyai Chemia, 2019)
Detection of bacterial volatile metabolites produced by human pathogenic bacteria is gaining continuous interest in both scientific and medical fields. Solid-phase microextraction (SPME) is a sampling technique that gained increasing attention in the last years due to its simplicity to implement and sensitivity. Volatile organic compounds (VOCs) released in the headspace over exudates infected with different bacteria were investigated in this work. GC-MS was involved for analysis. The above mentioned VOCs resulted from bacterial metabolism and the afferent processes that occur inside the biological samples. However, we identified 14 compounds emitted by the infecting pathogens, which can be assumed as bacterial markers.